1997
DOI: 10.1103/physrevlett.79.3759
|View full text |Cite
|
Sign up to set email alerts
|

Recoupling of Decoupled Vortex Liquid by Columnar Defects inBi2Sr2CaCu2

Abstract: We report on the effect of columnar defects on the interlayer phase coherence in Bi 2 Sr 2 CaCu 2 O 81y using Josephson plasma resonance as a probe. In the vortex liquid phase close to T c , the resonance field (H p ) shows a characteristic exponential temperature dependence similar to that of the irreversibility line. A drastic increase in H p occurs at a frequency-dependent temperature in the vortex liquid phase. We interpret this change as a manifestation of field-induced recoupling of decoupled vortex liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
44
1

Year Published

1998
1998
2000
2000

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 19 publications
7
44
1
Order By: Relevance
“…Note that due to the different effective measurement frequencies, f = 7.753 Hz in the ac shielding experiment versus f ∼ 10 −2 Hz for magnetization measurements using the SQUID, the H irr -values plotted in the Figure lie much above the apparent H irrvalues extracted from the closing of the magnetic hysteresis loops or merger of zero-field-cooled and field-cooled data obtained with a SQUID magnetometer. 8,[11][12][13] The same is indicated in Fig. 1(a), which shows the position of H irr determined from transmittivity measurements on the magnetization curve.…”
Section: B Relation With the Phase Diagrammentioning
confidence: 65%
See 3 more Smart Citations
“…Note that due to the different effective measurement frequencies, f = 7.753 Hz in the ac shielding experiment versus f ∼ 10 −2 Hz for magnetization measurements using the SQUID, the H irr -values plotted in the Figure lie much above the apparent H irrvalues extracted from the closing of the magnetic hysteresis loops or merger of zero-field-cooled and field-cooled data obtained with a SQUID magnetometer. 8,[11][12][13] The same is indicated in Fig. 1(a), which shows the position of H irr determined from transmittivity measurements on the magnetization curve.…”
Section: B Relation With the Phase Diagrammentioning
confidence: 65%
“…This is in contradiction to numerical work 57 and previous magnetization studies 13 which reported significant features in the phase diagram at µ 0 H a ≈ 1 3 B φ . Figure 7 shows that, whereas for the values of the matching field B φ = 1 and 2 T, most commonly investigated in the literature, [11][12][13]57 the fraction B φ /3 coincides with the crossover from regime (II) to regime (III) in H irr (T ), this is by no means true for other values of B φ . The results also show that the reported scaling of the irreversibility line with B φ reported in Ref.…”
Section: B Relation With the Phase Diagrammentioning
confidence: 75%
See 2 more Smart Citations
“…While the equilibrium magnetization is insensitive to the alignment of pancake vortices, we can compare its results to Josephson plasma resonance ͑JPR͒ experiments that do sense the pancake alignment. 17,18 These experiments directly probe the Josephson critical current along the c axis, itself determined by the relative phase shifts of the order parameter between layers and therefore by the correlations in pancake vortex distribution between the CuO 2 layers. In turn, the JPR cannot sense how many vortices are trapped on a columnar defect; its measurement is thus complimentary to that of the reversible magnetization.…”
Section: Rapid Communicationsmentioning
confidence: 99%